A racionalidade do não-racional: o sério problema da psicologia moral na Ética a Nicômaco de Aristóteles - Barreto, Carla da Silva (2024)
The investigation focuses on Aristotelian moral psychology, questioning how the desiderative element of the soul can be considered rational. Based on Nicomachean Ethics, the research explores the interaction between the rational and non-rational faculties of the soul, essential for the pursuit of happiness. Aristotle proposes that non-rational desire can be persuaded by practical reason to act in accordance with morality if there is harmonious communication between the faculties. Deliberate choice is presented as the result of this communicative excellence, where desire and reason come together in the act of choosing. Moral virtue is seen as the obedience of the non-rational. The persuasion of desire by reason is compared to a rhetorical process, where reason acts as a speaker who uses arguments to persuade desire. Persuasion is a process of convincing that uses tools such as rhetoric and poetry capable of influencing emotions and conduct. The desiderative faculty is considered rational because it can listen to and following reason. The thymós desire is highlighted for seeking the beautiful and noble, being essential in controlling the non-rational. Reason uses censure and praise to regulate appetites, appealing to emotions such as shame and modesty to avoid reprehensible acts. Topics such as honor, nobility, and beauty are used to persuade desire to act virtuously. Aristotle recognizes that rational persuasion is done by a spoken image, where deliberative reason resorts to imagination to create a discourse that reaches the non-rational. Metaphor is a linguistic resource that allows you to create and communicate this spoken image effectively, making a strong and persuasive impression on the thymós. The interaction between image and language in persuasive communication is explored in Rhetoric and Poetics. Tragedy is an example of how catharsis can purify the spectator's emotions, providing an experience that is both aesthetic and ethical. Thus, discuss how the non-rational faculty is considered “rational” to the extent that it can listen to and obeying reason, allowing it to be guided to a virtuous and happy life.